Colombian consensus recommendations for diagnosis, management and treatment of the infection by SARS-COV-2/ COVID-19 in health care facilities - Recommendations from expert´s group based and informed on evidence (2020)
The “Asociación Colombiana de Infectología” (ACIN) and the “Instituto de Evaluación de Nuevas Tecnologías de la Salud” (IETS) created a task force to develop recommendations for Covid 19 health care diagnosis, management and treatment informed, and based, on evidence. Theses reccomendations are addressed to the health personnel on the Colombian context of health services. © 2020 Asociacion Colombiana de Infectologia. All rights reserved.